Structure from diffraction methods - Bruce, Duncan W.; O'Hare, Dermot; Walton, Richard I. (Inorganic materials series., 2014)
"Part of the highly successful Inorganic Materials Series, this new title deals with recent advances in the characterisation of crystalline materials. This very timely volume complements the Series which has so far focused on particular classes of materials (synthesis, structures, chemistry and properties) by introducing and reviewing state-of-art techniques for materials characterisation. Written by experts from around the world, methods reviewed include spectroscopic, diffraction and surface techniques that examine the structure of materials on all length scales, from local atomic structure to long-range crystallographic order"--